Portable HiRes Multi-Channel Seismic Shot Data from J Anomaly Ridge and Southeast Newfoundland Ridge acquired during the R/V Knorr expedition KN179-01 (2004) ... - Norris, Richard (Interdisciplinary Earth Data Alliance (IEDA), 2013)
This data set was acquired with the LDEO Portable HiRes Multi-Channel Seismic system during R/V Knorr expedition KN179-01 conducted in 2004 (Chief Scientist: Dr. Richard Norris). These data files are of SEGY format and include Multi-Channel Reflection Seismic shot data that have not been processed. Data were acquired as part of the project: The Atlantic Deep Western Boundary Current During the Early Eocene Warm Period, and funding was provided by NSF grant: OCE02-21012. ...